Influences of the second motion probing gradient b-value and T2 relaxation time on magnetic resonance diffusion-derived ‘vessel density’ (DDVD) calculation: the examples of liver, spleen, and liver simple cyst - Ju, Zhi-Guo; Leng, Xiao-Ming; Xiao, Ben-Heng; Sun, Ming-Hua; Huang, Hua; Hu, Gen-Wen; Zhang, Ge; Sun, Ji-Hong; Zhu, Michael S. Y.; Guglielmi, Giuseppe; Wáng, Yì Xiáng J. (Quantitative imaging in medicine and surgery, 2025)
Magnetic resonance (MR) diffusion-derived 'vessel density' (DDVD) is calculated according to: DDVD = Sb0/ROI - S /ROI , where S and S refer to the tissue signal when -value is 0 or 2 s/mm . S and ROI can also be approximated by other low -values diffusion-weighted imaging (DWI). This study investigates the influence of the second motion probing gradient -value and T2 on DDVD calculations of the liver, spleen, and liver simple cyst. Literature analysis shows the liver and spleen have very similar amounts of perfusion. At 3T, liver and spleen have a T2 of around 42 and 60 ms respectively, while cyst has a very long T2. Twenty-eight subjects had 1.5T DWI data with -values of 0, 1, 2, 15, 20, 30 s/mm . Twenty-one subjects had 3.0T DWI data with -values of 0, 2, 4, 7, 10, 15, 20, 30 s/mm . DDVD , DDVD , DDVD , DDVD , DDVD , DDVD , DDVD , and DDVD were calculated from =0 and =1 images, =0 and =2 images, =0 and =4 images, =0 and =7 images, =0 and =10 images, =0 and =15 images, =0 and =20 images, =0 and =30 s/mm images, respectively. For liver simple cyst, two cysts totaling six slices scanned at 1.5T were available for DDVD measurement. At 1.5T, when the second -value was 1 s/mm , DDVD value was slightly higher than DDVD value; when the second -value was 2 s/mm , DDVD value was slightly higher than DDVD value. After that, the absolute difference between DDVD value and DDVD value became increasingly larger, with DDVD value being consistently higher. DDVD showed values close to 0 when the second -value was 1 s/mm . When the second -value was 20 or 30 s/mm , DDVD value was higher than DDVD value. The absolute DDVD values measured higher at 3.0T than at 1.5T. However, the ratio of DDVD to DDVD did not apparently differ between 1.5T and 3.0T. From the second -value being 2 s/mm onward, an increasingly larger second -value was associated with a trend of slow decreasing of the ratio of DDVD to DDVD . When a very low second -value is applied, the liver and spleen measure similar perfusions by DDVD, and cysts measure DDVD close to zero. When a higher second -value is applied, relative to the liver, the DDVD of spleen is suppressed while the DDVD of cyst is artificially promoted, which we consider are related to the T2 relaxation times of the liver, spleen, and cyst.